2018
DOI: 10.1016/s0140-6736(18)32561-3
|View full text |Cite
|
Sign up to set email alerts
|

Gathering momentum for the way ahead: fifth report of the Lancet Standing Commission on Liver Disease in the UK

Abstract: Much has been achieved over the past five years in describing the escalating burden of liver disease from lifestyle causes and the impact on hospital and primary care. The section on alcohol in this report reiterates the need for fiscal regulation by Government if overall consumption in the country is to be reduced to improve health, voluntary agreements with the drinks industry having repeatedly been shown to fail. The influence of the industry in its lobbying activities is highlighted in a separate account a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 50 publications
0
46
0
Order By: Relevance
“…There is a known shortfall in specialist liver services resources across the UK, which has led to the establishment of a Lancet Commission on liver disease . A number of other studies have reported on late mortality following hospitalisation for severe liver disease, and how it varies according to the cause of death, with much of the evidence from Scandinavia .…”
Section: Introductionmentioning
confidence: 99%
“…There is a known shortfall in specialist liver services resources across the UK, which has led to the establishment of a Lancet Commission on liver disease . A number of other studies have reported on late mortality following hospitalisation for severe liver disease, and how it varies according to the cause of death, with much of the evidence from Scandinavia .…”
Section: Introductionmentioning
confidence: 99%
“…An unmet clinical need is how to identify individuals in the general population with undiagnosed liver disease who are at risk of liver complications such as HCC . The early diagnosis of HCC is particularly important because of the poor prognosis and lack of curative options if HCC is diagnosed late in the course of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Some have specific goals, such as the Center for Indoor Air Research, which sought to undermine the evidence on the dangers of secondhand smoke 6. Others use a broad based approach that includes promotion of individual choice over collective action, supporting often ineffective educational campaigns rather than the legal or regulatory measures that tackle price, availability, and marketing of their products 7. This is exemplified in the use of the term “nanny state” to attack many of the most effective public health measures 8.…”
Section: Changing the Conversationmentioning
confidence: 99%